Boletín de la Real Academia Española: tomo 38 (1958), tomo 39 (1959). - Lope Blanch, Juan M. (El Colegio de México, 1962)
Se reseñó: Boletín de la Real Academia Española: tomo 38 (1958), tomo 39 (1959).